GEOSTATISTICS APPLIED TO BEST-FIT INTERPOLATION OF ORIENTATION DATA - Gumiaux C.; Gapais D.; Brun J.P. (My University, 2003)
Automatic methods used in geosciences to interpolate between orientation data have often limited applicability and strength, in particular where large ranges of orientations occur. In this paper, we show that geostatistical methods yield rather strong and powerful results when applied to directional data. The procedure involves the calculation of variograms, followed by a kriging interpolation of the data. In order to free from the circular property of directional data, the treatment of initial angular data sets is performed using scalar values provided by the direction cosines of double-angle values. The strength and application of the method are demonstrated by the analysis of theoretical and natural data sets. Natural examples are focused on the calculation and the analysis of cleavage trajectory maps.
Keywords: GEOSTATISTICS; INTERPOLATION; KRIGING; DIRECTIONAL DATA; CLEAVAGE TRAJECTORIES